Estudo e desenvolvimento de blendas ternárias biodegradáveis a partir de poli(ácido lático), poli(álcool vinílico) e quitosana - Grande, Rafael (Universidade Federal de São Carlos, 2010)
The present study examined the use of poly(vinyl alcohol) as a compatibilizing agent between chitosan and PLA and as a diluent for chitosan in an approach where a dispersion chitosan in PVA produced by solution blending these materials are added to PLA in an melting procedure. We investigate ternary mixtures of PLA / PVA / chitosan system both the PVA / chitosan and the blends of PLA / PVA / Chitosan studied here were plasticized with glycerol to reduce the melting point of PVA and chitosan. The ternary blends were processed in a Haake rheometer at 140 °C with rotation of 80rpm. Measurements of FTIR, DSC, DMA were performed to verify the degree of mixing and characterize these compounds. It was observed that the presence of the blend PVA / Chitosan PLA results in changes in the crystallization upon heating and the presence of two valleys fusion indicating immiscibility of the system. The morphology of the blends was evaluated by scanning electron microscopy. The positive results of this processing method is innovative and represents a major advance in the study of polymer blends from natural polymers processed by melt processing. However, the biggest loss in mechanical properties observed in the ternary blends as well as the darkening of the dispersed phase during drying, suggest that the presence of solvent waste are sufficient to promote matrix degradation during processing.
Keywords: Polímeros; Blendas poliméricas; Processamento por fusão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA